KONSEP DIRI ANAK JALANAN DI KABUPATEN REJANG LEBONG - Fadila, Fadila; Hartini, Hartini (JURNAL FOKUS KONSELING, 2017)
This study  aims  to  examine  how  the  concept  description Up  the  Streets  Age  Child  and Adolescent why the concept of self can be created. This research approach is mixed namely quantitative and qualitative, sample number 36 street children in Rejang Lebong regency. Sampling techniques using purposive sampling method. Instrument used to analyze the self-concept of street children by using questionnaires and interviews. The results of the study half of street children Rejang Lebong regency feel confident become street children, feel more responsible, feel more appreciated and feel independent. find the courage to face any conditions for forged by the various conditions that passed over in the street and had to be alert through the remains suspicious with people outside their community. Street children feel that they have to attract the pity of others and look Lusu, but street children are not in school can not chant, deceitful, communicate disrespectful and prone act of criminality Street children also feel the need to have a sense of mutual help and sensitive in particular with fellow community and controlling emotions sometimes a bit difficult to control.